Approximate methods for solving the boundary value problem of the theory of plasticity with complex loading - Bich, Dao Huy (Vietnam Journal of Mechanics, 1985)
In order to solve the non- linear boundary value problem of the theory of plasticity with complex loading different approximate methods are proposed as the followings: method of elastic solution, method of- variable elastic- parameters, method of finite elements combined with iterate method and others. Those methods transfer non- linear problem to a set of linear problems, problems of the theory of elasto plastic processes with middle curvature. The convergence of these principal method is considered.